Electrophysiological Investigations of the Effects of a Subanesthetic Dose of Ketamine on Monoamine Systems - El Iskandarani, Kareem S. (Université d'Ottawa / University of Ottawa, 2014)
Ketamine is a non-competitive NMDA antagonist that has been shown to have antidepressant properties both clinically as well as in preclinical studies when administered at a subanesthetic dose. In vivo electrophysiological recordings were carried in male Sprague Dawley rats 30 minutes following ketamine administration (10 mg/kg) to first assess its effects on monoaminergic firing. Whilst no change in the firing activity of serotonin (5-HT) neurons was observed in the dorsal raphe nucleus (DRN), an increase in the firing activity was observed for dopamine (DA) and noradrenergic (NE) neurons in the ventral tegmental area (VTA) and locus coeruleus (LC), respectively. The effect of ketamine on these electrophysiological parameters was prevented by pre-administration of the AMPA receptor antagonist NBQX 10 minutes prior to ketamine administration. In a second series of experiments, an increase in AMPA-evoked response was observed within 30 minutes in the CA3 layer of the hippocampus (HPC) following acute ketamine administration. These findings suggest that acute ketamine administration produces a prompt enhancement of AMPA transmission in the forebrain and also results in increased catecholaminergic activity. These effects may play a crucial role in the rapid antidepressant effects of ketamine observed shortly following its infusion in the clinic.
Keywords: Ketamine; Major depressive disorder; Monoamines; Glutamate; AMPA; NMDA